Safe Routes to School Planning for Improving Student Road Safety in Solok, Indonesia - Poetra, Andhika Dwiantara; Yossyafra, Yossyafra; Purnawan, Purnawan (Jurnal Teknik Sipil, 2026)
Traffic accidents involving students in educational areas remain a significant road-safety concern, particularly in areas with high traffic and limited safety facilities. This study aims to analyse student travel patterns, identify school travel routes, assess the need for safety facilities, and develop a Safe Routes to School (SRTS/RASS) concept along the Jalan KH. Dewantara corridor in Solok, Indonesia. Primary data were collected through road inventory surveys, pedestrian observations, and student interviews. Student travel patterns were analysed using an Origin–Destination (OD) matrix. The results show that the highest number of student trips originates from Zone 12 in Tanah Garam Urban Village, with 462 trips. Motorcycles dominate student transportation modes, accounting for approximately 60% of trips. The analysis identified six pedestrian routes, two bicycle routes, and one public transport corridor. The study proposes several safety improvements, including School Safety Zones (ZoSS), pelican crossings, sidewalk upgrades, bicycle lanes, and improved traffic signs and road markings to support safer mobility within the educational area.